A SPEECH ACT ANALYSIS OF WRITTEN ADVERTISEMENT OF COSMETIC BRAND IN INDONESIA - Nanda Aditria; Rissa San Rizqiya (IKIP Siliwangi, 2021)
Advertising is a tool for creating communication and can promote goods or other products to everyone or what customers call using binding language. Every language uses good language to attract customers. The main purpose of advertising is the point of view to promote and promise an item.This study used qualitative research from several cosmetic advertisements. This ad uses 16 types of speech acts, and out of 16 types of speech acts, only 10 brands are taken from cosmetic advertisements to attract or invite products to buy. And advertising results from 10 cosmetic brands in Indonesia only got 7% speech statement, 30% information, 9% claim, 19% suggestion, 9% suggestion, 2% argument, 2% accusation, 2% referral, 16% directive, persuasion 2%, promise 2%. From this result that most cosmetic brands in Indonesia use information, to make it more interesting for buyers to find out more information than other advertisements. Keyword :A speech act advertisement, cosmetic.